2019
DOI: 10.1111/jch.13599
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐phase blood pressure trajectories and clinical outcomes in ischemic stroke

Abstract: High blood pressure (BP) is frequent in acute ischemic stroke (IS). However, the impact of BP change patterns during acute phase on clinical outcomes is not conclusive. This study aims to investigate the association between the acute‐phase BP trajectories and clinical outcomes in IS patients with high admission BP. The cohort consisted of 316 IS patients with admission systolic BP (SBP) ≥160 mm Hg. SBP trajectories during the first 7 days after onset were characterized using a random effects model. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 29 publications
(76 reference statements)
3
31
0
Order By: Relevance
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…To prove the association of BPV and END, we adopted a definition of END as a ≥1‐point increase in NIHSS score during the first 72 hours after admission. And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies . And also, our findings were similar to that in the Chungs' study .…”
Section: Discussionsupporting
confidence: 92%
“…And, the rate of END was 32.5% in this study, which was consistent with the rates in previous studies. [4][5][6][7][8][9][10] And also, our findings were similar to that in the Chungs' study. 16 Both studies suggested that the acute in-hospital BPV was strongly associated with the risk of having a END.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations